A New Species of Mud Turtle of Genus Kinosternon (Testudines: Kinosternidae) from the Pacific Coastal Plain of Northwestern Mexico - Loc-Barragán, Jesús A.; Reyes-Velasco, Jacobo; Woolrich-Piña, Guillermo A.; Grünwald, Christoph I.; de Anaya, Myriam Venegas; Rangel-Mendoza, Judith A.; López-Luna, Marco A. (Zootaxa, 2020)
We describe a new species of mud turtle of the genus Kinosternon from the Pacific Coastal Plain of the Mexican states Sinaloa and Nayarit. The new species shares morphological characters with the recently described Kinosternon vogti, which are unique to these two turtles and separate them from the other species of the genus. The new species differs from K. vogti by skin coloration, size, and the scutellation of both carapace and plastron. We also present a molecular phylogeny of the family Kinosternidae based on two mitochondrial and four nuclear loci. Our results show that the new species is most closely related to K. vogti, and together they form the sister group to the K. hirtipes and K. integrum species groups of Kinosternon.